Predicting the Stock Market Efficiency in Weak Form: A Study on Dhaka Stock Exchange - Pervez, Masud; Rashid, Md. Harun Ur; Chowdhury, Md. Asad Iqbal; Rahaman, Mahbubur (International Journal of Economics and Financial Issues, 2018)
This study aims to examine the weak form efficiency of Dhaka Stock Exchange (DSE) using random walk model of EMH based on daily return series. The study applies both non-parametric [Kolmogorov-Smirnov test with Lilliefors coefficient, run test] and parametric test [autocorrelation test, unit root test and variance ratio test] on DSE general index, DSE broad index and DSE30 index ranging from June 1, 2004, to March 18, 2018. The results of the tests reject the null hypothesis of randomness. On the other hand, the result of the run test shows that share prices of DSE30 index follow the random walk. The return series of DSE broad index show some signs in favour of randomness by autocorrelation test while the returns of DSE general index support the efficiency concerning variance ratio test under both homoscedastic and heteroskedastic assumptions. The overall results of the study show inefficiency of DSE in the weak form which means the investor has a chance to make an abnormal profit predicting the historical data. This study also provides valuable insight to the shareholders, investors, the board of directors and regulatory bodies. Keywords: Stock market; Weak form efficiency; DSE; EMH. JEL Classifications: E44, G2